Determining Customer Relationship Management Strategy With Customer Personality Analysis Using Ontology Model Approach - Alya Rysda Ramadhanti; Rafa Syafiq Bastikarana; Andry Alamsyah; Sri Widiyanesti (Jurnal Manajemen Indonesia, 2020)
Indonesia is a market with attractive e-commerce growth in the past four years. The tight competition made the company try to find ways to maintain customer loyalty, including making improvements to the Customer Relationship Management (CRM) strategy. The way to establish a good CRM strategy is driven by a good approach from the company to customers. Through the process of understanding customer personality, major companies able to understand their customer behaviour, therefore, companies driven by their marketers can perform product marketing activities that are tailored to the tendency of the customer's personality. This research was conducted to determine the personality of the customer by utilizing data obtained from online reviews of several products using the ontology model approach. Personality is measured based on words and phrases given by customers through their online reviews with the help of the Big Five Personality theory in the classification process. The results of this study indicate that the measurement of personality using an ontology model reconstructed with the n-gram algorithm shows that customers on several products have different personalities. These personalities can be used as a foundation in determining and establishing CRM strategies in order to gain higher customer engagement. Keywords—Customer Relationship Management; Online Review; Ontology Model; Personality Measurement